Increasing Students' Mathematical Problem Solving Ability through the Realistic Mathematic Education (RME) Approach - Ahmad Sirojuddin; Naning Kurniawati; Ismanto Ismanto (Kontinu: Jurnal Penelitian Didaktik Matematika, 2023)
This research is a descriptive qualitative-quantitative research that aims to find out how to improve students' problem-solving abilities through the Realistic Mathematic Education (RME) learning model on social arithmetic material. The research was carried out at SMP Negeri 1 Sukosewu, with the selection of class VII C as the class studied with a total of 31 students. The method used is a mix method. The data collection techniques in this study are through observation, test techniques and interviews. Data analysis in this study is qualitative analysis with data triangulation and quantitatively which includes normality tests, summary models, coefficients and gain scores using the SPSS version 26 statistical application program with a significant level of 5%. The results of the coefficients test calculation obtained a significance value (2-tailed) of 0.000 < 0.05, which means that there is an increase in students' problem-solving ability through the Realistic Mathematic Education learning model and the results of the gain score calculation obtained a value of 0.7066. The conclusion of this study shows that there is an increase in students' problem- solving ability through the Realistic Mathematic Education (RME) learning model, the increase is "High".